Proteasome Composition and Activity Changes in Cultured Fibroblasts Derived From Mucopolysaccharidoses Patients and Their Modulation by Genistein - Pierzynowska, Karolina; Gaffke, Lidia; Jankowska, Elżbieta; Rintz, Estera; Witkowska, Julia; Wieczerzak, Ewa; Podlacha, Magdalena; Węgrzyn, Grzegorz (Frontiers in Cell and Developmental Biology, 2020)
In this study, we have asked whether proteasome composition and function are affected in cells derived from patients suffering from all types of mucopolysaccharidosis (MPS), an inherited metabolic disease caused by accumulation of undegraded glycosaminoglycans (GAGs). Moreover, we have tested if genistein, a small molecule proposed previously as a potential therapeutic agent in MPS, can modulate proteasomes, which might shed a new light on the molecular mechanisms of action of this isoflavone as a potential drug for macromolecule storage diseases. Significant changes in expression of various proteasome-linked genes have been detected during transcriptomic (RNA-seq) analyses in vast majority of MPS types. These results were corroborated by demonstration of increased proteasomal activities in MPS cells. However, GAGs were not able to stimulate the 26S proteasome in vitro, suggesting that the observed activation in cells is indirect rather than arising from direct GAG-proteasome interactions. Genistein significantly reduced proteasomal activities in fibroblasts derived from patients suffering from all MPS types, while its effects on in vitro 26S proteasome activity were negligible. Unexpectedly, levels of many proteasomal subunits were increased in genistein-treated MPS cells. On the other hand, this ostensible discrepancy between results of experiments designed for estimation of effects of genistein on proteasome activities and abundance of proteasomal subunits can be explained by demonstration that in the presence of this isoflavone, levels of ubiquitinated proteins were decreased. The genistein-mediated reduction of proteasomal activities might have beneficial effects in cells of MPS patients due to potential increasing of residual activities of defective lysosomal enzymes which would otherwise be subjected to efficient ubiquitination and proteasomal degradation as misfolded proteins. These results indicate another activity of genistein (apart from previously demonstrated reduction of GAG synthesis efficiency, stimulation of lysosomal biogenesis, and activation of the autophagy process) which can be beneficial in the use of this small molecule in treatment of MPS.